The impacts of government subsidy on SMEs during Covid-19 pandemic in Malaysia - Gayethiri, Tharmalingam (2023)
Purpose- To identify the types of government subsidy provided to SMEs and impact of government subsidy provided to SMEs during COVID-19 pandemic. Design/Methodology-This study uses qualitative research and content analysis whereby data analysis was conducted through questionnaire and phone call interview to identify the types of government subsidy and financial aid received during the pandemic and the impacts (business sustainability, labour issues and technology adoption) Findings- The results focused on background of SMEs, impact of government subsidy and financial aid received by SMEs during COVID-19 pandemic, particularly on business sustainability, labour issues and technology adoption. Findings shows that the seriousness of COVID-19 impact on SMEs in Malaysia diverge based on the nature of business. Research limitations- This result of the study is limited to only 20 SMEs in Malaysia. There is need for prolonged study and expanded observation sample. Practical implications-The findings of this paper able to contribute to the types and impacts of government subsidy and financial aid provided to SMEs during the pandemic which would provide useful insights to SMEs and relevant government agency policy. This study will be valuable for government non-governmental organisations (NGOs) to focus on problems faced by SMEs during the pandemic. Originality/Value-This study adds to the body of knowledge by focusing heavily on types of government subsidy and financial aid provided to SMEs during COVID-19 pandemic and the impact of government subsidy and financial aid on SMEs business during the pandemic.